Implementation of the I'DIS (Integrated Discipline) Application in Imposing Disciplinary Punishments on Civil Servants in Government Agencies in the Province of North Sulawesi - Simbawa, Desilia Swidia; Sampe, Stefanus; Monintja, Donald K. (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The use of the I'DIS Application in the implementation of the Imposition of Disciplinary Punishments for Civil Servants is indicated to be inconsistent between regulations and their implementation. Many Government Agencies in the working area of ​​the Regional Office XI BKN Manado still do not use the I'DIS Application and do not understand the input process or have not reached the stage of the process of making a Disciplinary Punishment Decree. This study aims to describe and analyze the Implementation of the I'DIS (Integrated Discipline) Application in the Imposition of Disciplinary Punishments for Civil Servants in Government Agencies in the Province of North Sulawesi. By using a qualitative design, it was found that the Implementation of the I'DIS Application in the imposition of disciplinary punishments for Civil Servants in Government Agencies in the Province of North Sulawesi still lacks a deeper understanding of the application, especially when technical guidance is carried out online. Likewise, resources including human resources, facilities and infrastructure are inadequate.